Estudio De La Brecha Empresario-Investigador: La Percepción Del Empresario - Carlos Ángel Méndez-Peón; Margarita Herrera-Avilés; Alfredo Toriz-Palacios; Manuel González-Pérez (European Scientific Journal, ESJ, 2017)
Competitiveness and productivity are crucial for the development of a country. A more competitive economy can grow faster over time. Technological innovation is the strongest pillar that guarantees long term competitiveness and quality of life for both developed and emerging countries. The University-Enterprise relationship (RUE) is a resource that is used to build a strong pillar of innovation. Therefore, it is important that a good relationship should be established between the main participants, the entrepreneur and the researcher (E-I). However, current literature has largely ignored the problem of the personnel involved. In contributing to the knowledge of this subject, we examined the gap that exists between the entrepreneur and the researcher (ERG), the importance of empathy in the E-I collaboration, and the factors that impact this collaboration the most from the entrepreneur stand point. The study was exploratory and transversal and data was gathered through interviews and questionnaires. The sample consisted of expert entrepreneurs with experience in innovation projects carried out in collaboration with researchers. The results show that 70% of the interviewed entrepreneurs recognize the existence of ERG. 87.5% of the entrepreneurs surveyed see empathy as a very significant factor for the E-I relationship, and there were 32 factors that are most influential on this collaboration.